ANALISIS TINGKAT PENGUNGKAPAN ELEMEN-ELEMEN INTEGRATED REPORTING PADA PT. ADARO ENERGY INDONESIA TBK DAN PT. ANEKA TAMBANG TBK - Larasati, Devira; Bhayangkara, IBK (Balance : Jurnal Akuntansi dan Bisnis, 2024)
This research uses qualitative methodology to analyze how PT Adaro Energy Indonesia Tbk (ADARO) and PT Aneka Tambang Tbk (ANTAM) disclose elements in the company's integrated annual report (integrated reporting) in 2022. The companies used as samples in the research It operate in the mining sector. The data analysis method used in this research is data collection, recording, analysis and interpretation of the results. Integrated Reporting has 8 elements of explanatory content, namely about the company and its environment, governance, business model, opportunities and risks, resource allocation and strategy, performance, prospects or future conditions, as well as the basis for planning and presentation. Based on the research results, it was found that the level of disclosure of integrated reporting elements at PT Adaro Energy Indonesia was included in the "good" or good category with a percentage of 79.07%. Meanwhile, PT Aneka Tambang Tbk showed an integrated reporting element disclosure level of 69.77% and was included in the "average" or quite good category.